2019
DOI: 10.5613/rzs.49.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Parenthood among LGBTIQ People in Croatia: Who Wants to Become a Parent and How?

Abstract: Lesbian, gay, bisexual, transgender, intersex and queer (LGBTIQ) people can become parents using various methods, but actual possibilities differ between countries depending on the legislation and social norms. The main goal of this study was to explore parenting desire and family formation methods among LGBTIQ people in Croatia. Differences in parenting desire based on sociodemographic characteristics, the frequency and use of family formation methods, as well as the importance of different sources of support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
1
1
0
1
Order By: Relevance
“…This trend is in line with the studies for Poland (Mizielińska et al, 2015), Croatia (Štambuk et al, 2019), andHungary (Háttér Társaság, 2017), wherein it was found that although most children in same-sex families were born in one of the parents' previous oppositesex relationship, young gay men and lesbians prefer other ways to parenthood. Despite the severe barriers to gay parenthood persist in these countries, information on same-sex families is becoming more accessible.…”
Section: Discussionsupporting
confidence: 88%
“…This trend is in line with the studies for Poland (Mizielińska et al, 2015), Croatia (Štambuk et al, 2019), andHungary (Háttér Társaság, 2017), wherein it was found that although most children in same-sex families were born in one of the parents' previous oppositesex relationship, young gay men and lesbians prefer other ways to parenthood. Despite the severe barriers to gay parenthood persist in these countries, information on same-sex families is becoming more accessible.…”
Section: Discussionsupporting
confidence: 88%
“…Takový trend byl zaznamenán i v některých dalších postsocialistických zemích (např. Švab 2007;Mizielińska et al 2015;Takács 2018;Štambuk et al 2019) a ČR patří v rámci tohoto regionu k zemím v daném ohledu progresivnějším (např. Nešporová 2021).…”
Section: Diskuse a Závěrunclassified
“…Even so, many nonheterosexual individuals establish same-sex families with limited or no legal recognition and, in increasing numbers, pursue planned parenthood in their countries in the European East (e.g. in Poland: Mizielińska and Stasińska, 2019; in Croatia: Štambuk et al, 2019) or the Global South (e.g. in China: Wei, 2021); regardless that these countries are often labeled ‘oppressive’ at the sexual freedoms maps of the world.…”
mentioning
confidence: 99%